King's College of Household and Social Science and the household science movement in English higher education, c. 1908-1939 - Blakestad, N; Blakestad, Nancy L. (1994)
﻿ This thesis is an account of the 'household and social science' course opened at King's College for Women in 1908 and its evolution up to 1939. The course was a significant departure for women's higher education in England as it was the first attempt to define a special university discipline based upon women's 'domestic' roles. However, historical accounts of women's higher education have either ignored or dismissed it, largely because of the predominance of'separate spheres' analyses in the historiography of women's higher education of the 1970s and early 1980s. Such accounts have presented the household science course in a negative light because of its 'domestic' image. This thesis thus offers a reassessment of the household science movement and those who supported it. The 'household science' concept owed its origin to the American 'home economies' movement which originated in the mid-nineteenth century. Chapter 1 provides a history of the home economics movement in America, tracing its evolution in the context of women's higher education until 1914. Initially home economics was seen as a 'vocational homemaking' course aiming to train women for home life. At the turn of the century, however, a 'scientific' model was developed by women scientists in order to promote research into social problems connected with the domestic sphere. These two models~the vocation and the scientific, have developed in tandem in American home economics. Chapters 2 and 3 consider the origins and early evolution of the 'household science' course in England, which was largely influenced by the American 'scientific' model. Chapter 2 first considers the concept of domestic education in the history of women's education and factors that precluded the development of a 'vocational homemaking' course in English higher education. The rest of the chapter analyses the origins of the household science movement in its social and intellectual context, in particular its connection with Edwardian preoccupations with 'physical deterioration' and infant mortality. Like their American counterparts, the founders of the course saw household science as a reform movement which aimed to promote research into domestic problems such as hygiene and nutrition, as well as to create a more useful and relevant university discipline for women's domestic roles, whether as housewife/mother or in 'municipal housekeeping' roles. Chapter 3 discusses the household science course from a disciplinary standpoint, looking at how the syllabus was constructed, the contemporary educational controversies it engendered, and its evolution up to 1920 when the B.Sc. degree was granted. Chapters 4, 5, and 6 examine the main factors which ultimately undermined the success of household science as a discipline. Chapter 4 evaluates career trends amongst KCHSS students from 1910-49, analysing to what extent the KCHSS administration was able to create a professional career structure for the household science discipline. The interplay between administrative policy, career trends, and professionalization is analyzed in relation to three career fields-social welfare, laboratory research, and dietetics. Chapters considers the professional conflicts between KCHSS and the domestic subjects teaching profession. Chapter 6 analyses KCHSS's failure to carve out a unique academic 'territory' or expertise and the various factors that affected this. The final chapter assesses how successful KCHSS was as an institution, looking at how students themselves experienced the course, their motivations for taking it, and its impact on their lives. Although household science was unsuccessful as a discipline, the course did give students a wide choice of career options, creating openings in less conventional spheres for women who did not want to teach and providing opportunities for the less-able student to follow a scientific career. The conclusion considers how the social climate of the interwar period affected the working out of the original household science ideals.